# Ngô Quốc Anh

## May 16, 2010

### Conformal Changes of Riemannian Metrics

Filed under: Riemannian geometry — Tags: — Ngô Quốc Anh @ 5:54

I guess I will use the relation between curvature tensors of metrics lying in a conformal class frequently so I decide to post something related to this stuff which may be helpful and we can use later. Actually, I have used it when we proved conformal Laplacian operator is invariant. Let us briefly recall some terminologies

Definition (conformal). Two pseudo-Riemannian metrics $g$ and $\widetilde g$ on a manifold $M$ are said to be

1. (pointwise) conformal if there exists a $C^\infty$ function $f$ on $M$ such that $\displaystyle \widetilde g=e^{2f}g$;

2. conformally equivalent if there exists a diffeomorphism $\alpha$ of $M$ such that $\alpha^* \widetilde g$ and $g$ are pointwise conformal.

Note that, if $g$ and $\widetilde g$ are conformally equivalent, then $\alpha$ is an isometry from $e^{2f}g$ onto $\widetilde g$. So we will only study below the case $\widetilde g = e^{2f}g$. Our aim is to compare Riemann curvature, Scalar curvature, Ricci curvature,… of $g$ and $\widetilde g$.

Definition (the Kulkarni–Nomizu product). This product $\odot$ is defined for two $(0,2)$-tensors and gives as a result a $(0,4)$-tensor. Precisely, $\displaystyle \alpha \odot \beta (X_1,X_2,X_3,X_4)=\alpha (X_1,X_3)\beta (X_2,X_4)+\alpha (X_2,X_4)\beta (X_1,X_3)-\alpha (X_1,X_4)\beta (X_2,X_3)-\alpha (X_2,X_3)\beta (X_1,X_4)$

or $\displaystyle {(\alpha \odot \beta )_{ijkl}} = {\alpha _{il}}{\beta _{jk}} + {\alpha _{jk}}{\beta _{il}} - {\alpha _{ik}}{\beta _{jl}} - {\alpha _{jl}}{\beta _{ik}}$.

Levi-Civita connection. On $(M,g)$, the Levi-Civita connection $\nabla$ is an affine connection which is torsion free $\displaystyle \nabla_XY+\nabla_YX=[X,Y]$

and satisfies the rule $\displaystyle X(g(Y,Z))=g(\nabla_X Y,Z) + g(Y, \nabla_X Z)$

for any vector fields $X,Y,Z$. We now have $\displaystyle {\widetilde\nabla _X}Y = {\nabla _X}Y + X(f)Y + Y(f)X - g(X,Y) {\rm grad}f$.

Weyl tensor. This tensor is defined to be $\displaystyle W = R - \frac{1}{{n - 2}}\left( {{\rm Ric} - \frac{{\rm Scal}}{n}g} \right) \odot g - \frac{{\rm Scal}}{{2n(n - 1)}}g \odot g$.

Thus we have the rule $\displaystyle\widetilde W =W$.

Ricci tensor. This is a $(2,0)$-tensor defined by $\displaystyle {\rm Ric}(X,Y) = {\rm Trace}( x \to R(x, X)Y)$.

In local coordinates, it has the form $\displaystyle {\rm Ric} = R_{ij} dx^i \otimes dx^j$.

So we have the following rule $\displaystyle\widetilde{\rm Ric} = {\rm Ric} - (n - 2)({\rm Hess} f -{\rm grad}f \otimes {\rm grad}f) + (\Delta f - (n - 2)|{\rm grad}f|^2)g$.

Traceless Ricci tensor. This tensor is defined by $\displaystyle\displaystyle {Z_{ij}} = {R_{ij}} - \frac{1}{n}{\rm Scal}{g_{ij}}$.

A simple calculation shows that its trace, $g^{ij}Z_{ij}$, equals zero. So $\displaystyle\widetilde Z = Z - (n - 2)\left( {{\rm Hess}f - {\rm grad}f \otimes {\rm grad}f} \right) - \frac{{n - 2}}{n}\left( {\Delta f + |{\rm grad}f|^2} \right)g$.

Scalar curvature. This $(2,0)$ tensor is defined to be the trace of Ricci tensor, that is $\displaystyle {\rm Scal} = {\rm Trace}( {\rm Ric}) = g^{jk}{\rm Ric}_{jk}$.

So $\displaystyle\widetilde{\rm Scal} = {e^{ - 2f}}\left[ {{\rm Scal} + 2(n - 1)\Delta f - (n - 2)(n - 1)|{\rm grad} f{|^2}} \right]$.

In practice, this conformal change is not useful, we usually use the following conformal change $\displaystyle \widetilde g=f^\frac{4}{n-2}g$.

With this, we simply have $\displaystyle - \Delta f + \frac{{n - 2}}{4(n - 1)}{\rm Scal}f = \frac{{n - 2}}{4(n - 1)}\widetilde{{\rm Scal}}{f^{\frac{{n + 2}}{{n - 2}}}}$

or $\displaystyle \widetilde{{\rm Scal}} = {f^{ - \frac{{n + 2}}{{n - 2}}}}\left[ { - \frac{4(n - 1)}{n - 2}\Delta f + {\rm Scal}f} \right]$.

Riemann curvature tensor. This $(1,3)$ tensor is defined to be $\displaystyle R(X,Y)Z = \nabla_X \nabla_YZ - \nabla_Y \nabla_XZ - \nabla_{[X,Y]}Z$.

In local coordinates, we get $\displaystyle R = R_{ikl}^j\dfrac{\partial }{{\partial {x^j}}} \otimes d{x^i} \otimes d{x^k} \otimes d{x^l}$.

So $\displaystyle \widetilde R = {e^{2f}}\left[ {R - g\odot\left( {{\rm Hess}f - {\rm grad}f \otimes {\rm grad}f + \frac{1}{2}|{\rm grad}f{|^2}g} \right)} \right]$.

Volume element. This, $d{\rm vol}_g$, is the unique density such that, for any orthonormal basis $(X_i)$ of $T_XM$, $\displaystyle d{\rm vol}_g(X_1,...,X_n)=1$.

In local coordinates, $\displaystyle d{\rm vol}_g = \sqrt{|g|} dx^1\wedge \dots \wedge dx^n$.

So $\displaystyle d{\rm vol}_{\widetilde g} = e^{nf}d{\rm vol}_g$.

Hodge operator on $p$-forms (if $M$ is oriented). The Hodge star operator on an oriented inner product space $V$ is a linear operator on the exterior algebra of $V$, interchanging the subspaces of $k$-vectors and $n-k$-vectors where $n = \dim V$, for $0 \leqslant k \leqslant n$. It has the following property, which defines it completely: given an oriented orthonormal basis $e_1,e_2,\dots,e_n$ we have $\displaystyle *(e_{i_1} \wedge e_{i_2}\wedge \cdots \wedge e_{i_k})= e_{i_{k+1}} \wedge e_{i_{k+2}} \wedge \cdots \wedge e_{i_n}$.

One can repeat the construction above for each cotangent space of an $n$-dimensional oriented Riemannian or pseudo-Riemannian manifold, and get the Hodge dual $n-k$-form, of a $k$-form. The Hodge star then induces an $L^2$-norm inner product on the differential forms on the manifold. One writes $\displaystyle (\eta,\zeta)=\int_M \eta\wedge *\zeta$

for the inner product of sections $\eta$ and $\zeta$ of $\Lambda^k(M)$. (The set of sections is frequently denoted as $\Omega^k(M) = \Gamma(\Lambda^k(M)$). Elements of $\Omega^k(M)$ are called exterior $k$-forms). For example, for a positively oriented orthogonal cofram $\{\omega^i\}_1^n$, one has $\displaystyle *(\omega^1 \wedge \cdots \wedge \omega^p)=\omega^{p+1}\wedge \cdots \wedge \omega^n$.

So $\displaystyle {*_{\widetilde g}} = {e^{(n - 2p)f}}{*_g}$.

Codifferential on $p$-forms. This notion $\delta$ is usually defined through the exterior derivative $\displaystyle d : \Omega^p(M) \to \Omega^{p+1}(M)$

by the following rule (also called the formal adjoint of exterior derivative) $\displaystyle\langle \eta,\delta \zeta\rangle = \langle d\eta,\zeta\rangle$,

i.e. $\displaystyle \delta : \Omega^p(M) \to \Omega^{p-1}(M)$.

In other words, for a $p$-form $\beta$, $\displaystyle \delta \beta = {( - 1)^{np + n + 1}}*d*\beta$.

So $\displaystyle\widetilde\delta \beta = {e^{ - 2f}}\left[ {\delta \beta - (n - 2p){\iota_{{\rm grad}f}}\beta } \right]$

where $\iota$ denotes the interior product (the contraction of a differential form with a vector field).

(pseudo-) Laplacian on $p$-forms. This is known as the Hodge Laplacian and also known as the Laplace–de Rham operator. It is defined by $\displaystyle\Delta= d\delta+\delta d$.

An important property of the Hodge Laplacian is that it commutes with the $*$ operator, i.e. $\Delta * = * \Delta$.

So $\displaystyle\widetilde\Delta \alpha = {e^{ - 2f}}\left[ {\Delta \alpha - (n - 2p)d({\iota_{{\rm grad}f}}\alpha ) - (n - 2p - 2){\iota_{{\rm grad}f}}d\alpha + 2(n - 2p){\rm grad}f \wedge {\iota_{{\rm grad}f}}\alpha - 2{\rm grad}f \wedge \delta \alpha } \right]$.

See also: Arthur L. Besse, Einstein manifolds, Ergebnisse der Mathematik und ihrer Grenzgebiete, Springer-Verlag, 1987.

## Leave a Comment »

No comments yet.

This site uses Akismet to reduce spam. Learn how your comment data is processed.